Analysis of The Risk of MSDS Occurrence in Female Coconut Peeler Workers - Muchliza Rizwany; Putra Apriadi Siregar (International Archives of Medical Sciences and Public Health, 2021)
Introduction: Musculoskeletal disorders are pains experienced byindividuals in their muscles and skeletons. Awkward postures, staticpostures, and repetitive movements can all contribute to thedevelopment of musculoskeletal disorders. The purpose of this studyis to examine the relationship between work posture andmusculoskeletal disorders among coconut peeler workers in thevillage of Sei Apung. Method: This is a cross-sectional quantitativestudy. 52 workers were chosen for this study using a purposivesampling technique. The data were collected using the Rapid EntireBody Assessment (REBA) and Nordic Body Map (NBM)questionnaires.Result : This study discovered that the samplecharacteristics for the age range were dominated by individuals aged> 30 years, totalling 29 individuals (55.8 per cent). This study'srespondents were entirely female. With an average work period ofone to five years (63.5 per cent), respondents work an average of fivehours per day (75 per cent), and respondents' most recent education isdominated by high school graduates or equivalent (76.9 percent).Conlusion As a suggestion for taking a break or stretchingmuscles, adding hand braces or elbow braces to reduce the risk ofcomplaints, and modifying the seat to reduce the risk of lower backcomplaints.